Relationship Between Cariogenic Food Consumption Patterns and Brushing With the Event of Dental Caries in Early Childhood - Kiftiyah, Kiftiyah; Nur Rosyidah, Nanik (Universitas Islam Lamongan, 2022)
Dental caries is a major problem in the oral cavity today. Preschool children have a high susceptibility to dental caries caused by the activity of a microorganism in a fermentable carbohydrate characterized by demineralization of the hard tooth tissue and followed by the breakdown of organic matter. Children's dental health plays a role in children's growth and health. The problem in this study is the high incidence of dental caries in children under five.The design of this research is analytic with a cross sectional approach. Sampling using Simple Random Sampling technique. The population in this study were all children aged 3-5 years in Early Childhood Education Programs Sooko Mandiri I. The sample obtained was 38 respondents in October 2021. Data were collected using a closed questionnaire and observation sheets filled out by the researcher. After that, the data was tabulated and analyzed using Cross Tabulation and Linear Regression. The results showed that most of the respondents were in the category of cariogenic food consumption with a frequency of sometimes 50%, while most of the respondents were in the category of brushing their teeth with an occasional frequency of 52.7%. Based on the Linear Regression test with p < 0.05, the p value for the relationship between cariogenic food consumption patterns and dental caries and tooth brushing patterns with dental caries was 0.57. Thus there is no relationship between the consumption pattern of cariogenic food and the habit of brushing teeth with the incidence of dental caries. Seeing the results of this study, it is still necessary to have periodic counseling in order to further improve the habit of brushing children's teeth and reduce children's consumption patterns of cariogenic foods.